Divergent Trajectories of BMI over Age for Adult Baka Pygmy People and their Sympatric Non-Pygmy Populations - Funk, S.M.; Guerra, B.P.; Mena Martínez, N. de; Ickowitz, A.; Fa, J.E. (Springer, 2020)
Differences in socioeconomic conditions and health have been reported for African Pygmies and their sympatric populations of other ethnic groups. We collected anthropometric data in southern Cameroon from Baka and their Bantu neighbours, and also extracted data from the five available and representative Demographic and Health Surveys (DHS) in sub-Saharan African countries that have Pygmy populations..Our results show that the Baka exhibited a weak but significant decline of body mass index (BMI) with age (p = 0.003) without a sex difference. At a larger geographical scale, all five DHS surveys revealed flat or negative slopes for Pygmy BMI with age. Except for one non-Pygmy ethnic group, the slope was less than for all DHS- surveyed non-Pygmy African ethnicities. Pygmy populations were the least wealthy in all surveys, but no pattern for anaemia levels versus BMI emerged. We argue that the declining or stagnant trajectory of Pygmy BMI over age is most concerning, since this sets them apart not only from all other ethnic groups in the region, but from the general trend of increasing body weight over age. We suggest that our results do not reflect the influence of ethnicity per se, but the fact Pygmy populations are socially and materially deprived groups. These findings are fully aligned with the extraordinary high premature death rate among the Baka and need to be addressed for sustainable development initiatives to be effectively implemented.